Development of production of coarticulation in children - P.G, Ganesh Perumal (Journal of All India Institute of Speech and Hearing)
Coarticulation may be defined as a speech production process in which the coarticulatory characteristics, features or properties of one sound are modified by another sound. Evidences for the presence, different types & extent of coarticulation have come from physiological, acoustical and perceptual study. The extent or magnitude of coarticulation is highlighted by the physiological and acoustical studies.